Peran Media Massa Lokal Dalam Membentuk Opini Publik Saat Tanggap Darurat Gempa 6,3 Magnitudo Di Bengkulu - Mukhlizar; Linda Safitra (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
For Indonesians living in earthquake-prone areas, natural disasters pose a significant threat. One such event occurred in Bengkulu Province, which was struck by a 6.3 magnitude earthquake at 8:34 PM WIB on May 28, 2025. This study examines how local mass media influenced public sentiment during the emergency response to the 6.3 magnitude earthquake that shook Bengkulu on May 28, 2025. During the crisis, local media such as PedomanBengkulu.com, LensaBengkulu.com, RBTV, Rakyat Bengkulu, and Bengkulu Ekspress played an important role in providing information and calming the public. This study examines how local media coverage affects public perceptions of disaster risk, government reactions, and mitigation strategies using a literature study methodology. The findings show that local media usually avoid speculative news and prioritize news that is educative, calming and informative. By using news framing based on reliable information and official sources, local media are able to build community involvement in disaster response, foster positive collective opinion and increase public trust. Public communication management in emergency situations, especially in disaster-prone areas, can be improved through the theoretical and practical contributions of this research.